Endobronchial ultrasound elastography - Dietrich, Christoph F.; Jenssen, Christian; Herth, Felix (Endoscopic ultrasound, 2016)
Elastographic techniques have recently become available as advanced diagnostic tools for tissue characterization. Strain elastography is a real-time technique used with transcutaneous ultrasound (US) and endoscopic US. Convincing evidence is available demonstrating a significant value of strain elastography for the discrimination of benign and malignant lymph nodes (LNs). This paper reviews preliminary data demonstrating the feasibility of performing real-time elastography during endobronchial US (EBUS) and a potential application of this technique for selection of LNs for EBUS-guided transbronchial needle aspiration in patients with lung cancer and extrathoracic malignancies.
Gesehen am 08.05.2020